OFFERS FOR INDEXATION MECHANISM OF INSURANCE PENSION IN MANDATORY PENSION INSURANCE SYSTEM - A. Sil'chuk (Модернизация, инновация, развитие, 2016)
The main problem of mandatory pension insurance system is lack of monetary resources on payment of pensions. One of the key mechanisms of ensuring of financial stability of the system is indexation insurance pensions, so long as through indexation it is possible to regulate the stream of monetary resources of both budget of pension fund and federal budget's transfer payments.Objectives. The aim of this work is to form a suggestion upon settlement of indexation of insurance pension for ensuring of financial stability of the pension system.Methodology. Writing the article applied methods used in economic studies: analysis, analytical, comparative, induction.Results. The author finds the basic problems of existent mechanism of indexation of pensions and gives suggestions about development of indexation mechanism.Conclusions and Relevance. New approach can be easily applicable in any macroeconomic and demographic terms and allow to manage federal budget expenditures inclusive of its resource possibilities.